2022
DOI: 10.1007/s41208-022-00396-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Boundary Habitat Continuity on Spillover from a Mediterranean Marine Protected Area

Abstract: The effectiveness of marine protected areas (MPAs) to restore populations of exploited species, both within and outside of their boundaries through net movement of individuals (“spillover”), can potentially be affected by continuity of habitats across the boundaries. Sandy seabeds may reduce movement of reef-associated species across MPA boundaries, thereby increasing the ‘reserve effect’ while decreasing spillover. Underwater visual censuses were undertaken inside the Cerbère-Banyuls Marine Reserve (CBMR) (Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…2008; Pinillos and Riera, 2022). Previous work (Albano et al, 2021) in this study identified shared habitat preferences between smooth hammerhead sharks and commercially targeted smooth hound sharks (Mustelus spp.).…”
Section: Discussionmentioning
confidence: 71%
“…2008; Pinillos and Riera, 2022). Previous work (Albano et al, 2021) in this study identified shared habitat preferences between smooth hammerhead sharks and commercially targeted smooth hound sharks (Mustelus spp.).…”
Section: Discussionmentioning
confidence: 71%